1995
DOI: 10.1002/jcla.1860090303
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of c‐erbb‐2 proteins in sera from patients with carcinomas and in breast tumor tissue cytosols: Correlation with serum tumor markers and membrane‐bound oncoprotein

Abstract: Using a commercial kit with antibodies against the ectodomain of c-erbB-2 protein, we detected c-erbB-2 immunoreactivity in human serum. We found that the percentages of patients with elevated serum c-erbB-2 immunoreactivities were 35, 21, and 9% in breast, prostate, and ovarian carcinoma, respectively. The majority of the elevated immunoreactivities were associated with sera containing highly elevated tumor markers with the highest in breast carcinoma (35%) and lowest in ovarian cancer (9%). Excellent correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…Moreover, activation of the HER2 kinase signaling cascade can constitutively activate the androgen receptor and render prostate cancer cells refractory to androgen receptor inhibition in different model systems (29,34,37,38). Circulating levels of HER2 have been correlated with gene amplification and tissue overexpression (39,40). Taken together, these data suggest that preoperative plasma HER2 is a marker of early, clinically occult prostate cancer metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, activation of the HER2 kinase signaling cascade can constitutively activate the androgen receptor and render prostate cancer cells refractory to androgen receptor inhibition in different model systems (29,34,37,38). Circulating levels of HER2 have been correlated with gene amplification and tissue overexpression (39,40). Taken together, these data suggest that preoperative plasma HER2 is a marker of early, clinically occult prostate cancer metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…Wu et al [17] first demonstrated that this protein is released in the circulation of prostate cancer patients. In their report, the distribution of tumor stages or disease statuses was not clarified.…”
Section: Discussionmentioning
confidence: 97%
“…They showed an increased level of the protein in sera of 3 of 12 patients with breast cancer, raising the possibility of using serum c-erbB-2 determination as a diagnostic and monitoring tool for c-erbB-2 positive carcinoma. Recently, Wu et al [17], reporting on the measurement of c-erbB-2 protein in sera from patients with prostate cancer, demonstrated that 21% (49/234) of the patients with prostate cancer had elevated serum levels of c-erbB-2 protein. In their report, however, the potential as a biomarker was not fully studied.…”
Section: Introductionmentioning
confidence: 97%
“…The extracellular domain of the HER-2/»«/ receptor can be found in soluble form in the sera of patients with breast cancer [16][17][18][19]. The biological importance of solu ble HER-2/»«/ is highlighted by the fact that certain stud ies have indicated a close correlation of high HER-2/»«/ oncoprotein serum levels with an aggressive course of breast cancer [20].…”
Section: Introductionmentioning
confidence: 99%